"Identity" among the minority Slovenes of Carinthia, Austria - Priestly, Tom (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
Members of the Slovene-speaking minority in Carithia, Austria, have several "identities" at their disposal, ranging from the local to the supranational and including terms reflecting citizenship and language. We asked subjects from this minority which "identity labels" they felt most comfortable with. The results werw largely as expected; they show a number of distinctions according to the age and educational level of the subjects, and in particular:the younger and the better-educated the subjects, the greater the preference for the labels "Carinthian Slovene" and "Slovene" rather than "Austrian" and "carinthian". This suggests a positive future for the maintenance of Slovene identity and language in this province.
Keywords: Austria; Avstrija; Koroška; zamejski Slovenci; narodna identiteta; etničnost